2007
DOI: 10.5964/ijpr.v1i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Examining Equity Theory across Cultures

Abstract: In order to better understand culture's role between perceived equity in one's romantic relationship and relationship satisfaction, we sampled two groups from different cultural backgrounds and attempted to answer the question of whether culture would impact the relationship between equity and relationship satisfaction. We interviewed men and women from the University of Hawai'i (UH), a relatively individualist culture, and from the University of the West Indians in Jamaica (UWI), considered a more collectivis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown that lack of reciprocity is negatively related to employees' physiological and psychological well-being (Schaufeli, 2006). Aumer-Ryan et al (2007), for example, found the European American and the Asian-American groups were far less satisfied in under-benefited than in balanced and in over-benefited in close relationships. Nevertheless, those who are feeling over-benefited -i.e.…”
Section: Job Demands and Resourcesmentioning
confidence: 99%
“…Numerous studies have shown that lack of reciprocity is negatively related to employees' physiological and psychological well-being (Schaufeli, 2006). Aumer-Ryan et al (2007), for example, found the European American and the Asian-American groups were far less satisfied in under-benefited than in balanced and in over-benefited in close relationships. Nevertheless, those who are feeling over-benefited -i.e.…”
Section: Job Demands and Resourcesmentioning
confidence: 99%
“…Family life is central to most Jamaicans and extended family structures are the norm (Aumer‐Ryan, Hatfield, & Fray, ). The concept of family is not limited to just the household but applies to blood and non‐blood kin as kinship bonds extend to close friends and neighbours who contribute to the nurturing and rearing of children.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in the United States indicate that couples consider social justice to be crucial, and considerations of equity have been found to determine who falls in love with whom, mate selection, sexual satisfaction, willingness for extramarital affairs (see Hatfield et al, 2008 for a review). But the notion of social justice in the U.S. is tied to the dominant view of U.S. capitalism -"the more time and energy you invest, the more you're entitled to" (Aumer-Ryan, Hatfield, & Frey, 2007). Surprisingly little studies have been conducted outside the US (with the exception of studies by Bram Buunk and Nico Van Yperen in the Netherlands), and there are even fewer studies conducted in collectivistic cultures of East Asia, or in countries of Central and Eastern Europe.…”
Section: Introductionmentioning
confidence: 99%